A cross-sectional survey of dentists' use of digital radiographic techniques in Riyadh, Saudi Arabia - Ra'ed Al Sadhan (Wolters Kluwer Medknow Publications, 2021)
Introduction: Undergraduate oral and maxillofacial radiology curricula are currently undergoing a reform process that is moving toward digital-based radiology that requires dedicated resources to train dental students to the field experience. It is not known if the time is appropriate to totally shift from training students on conventional analog film-based radiology to training them on digital images and the choice of digital system in intraoral and extraoral radiography. Aim: The aim of this study is to assess availability and utilization of the digital radiographic techniques by dental clinics in Riyadh, Saudi Arabia, using a cross-sectional descriptive, epidemiological survey. Materials and Methods: The study included dental departments of nine main governmental hospitals, six dental schools in Riyadh and a representative selected sample of the private dental clinics in Riyadh that included 40 dental clinics. A self-administered e-survey regarding the use of analog or digital radiographic intraoral and extraoral techniques was made. Descriptive statistics are reported in forms of means and range. Results and Discussion: For intraoral radiographic examinations, most clinics (90.9%) used digital systems. Solid-state detectors such as charge-coupled device (CCD) and complementary metal oxide semiconductor sensors were the most popular type digital intraoral sensors (94%) and only 13 locations (26%) used digital photostimulable phosphors plates. For panoramic radiography, almost all (98.1%) used digital systems. Again, the solid-state detectors were the most common digital panoramic system (96.4%). Most respondents had a digital information system to store, retrieve, and display digital radiographs (92.7%), whereas only four locations (5.9%) used hard-copy films or paper prints. Conclusion: Digital imagining is more common than film-based imaging in intraoral radiography in and panoramic radiography in the different dental care delivery sites in Riyadh, Saudi Arabia.